106k views
5 votes
Which expression is equal (x+4)(-3x^2-4x+2)

Which expression is equal (x+4)(-3x^2-4x+2)-example-1
User Unnie
by
5.6k points

1 Answer

1 vote

Answer:

-3x^3-16x^2-14x+8

Explanation:


(x+4)(-3x^2-4x+2)\\\\Distribute\:parentheses\\\\=x\left(-3x^2\right)+x\left(-4x\right)+x*\:2+4\left(-3x^2\right)+4\left(-4x\right)+4* \:2\\\\Apply\:minus-plus\:rules\\+\left(-a\right)=-a\\\\=-3x^2x-4xx+2x-4*\:3x^2-4*\:4x+4*\:2\\\\Simplify\\-3x^2x-4xx+2x-4*\:3x^2-4*\:4x+4*\:2:\\\\\quad -3x^3-16x^2-14x+8\\\\=-3x^3-16x^2-14x+8

User Saurav Kumar
by
6.0k points